Approximative characteristics of the Nikol'skii-Besov-type classes of periodic functions in the space $B_{∞,1}$ - Fedunyk-Yaremchuk, O.V.; Hembars'kyi, M.V.; Hembars'ka, S.B. (Carpathian Mathematical Publications, 2020)
We obtained the exact order estimates of the orthowidths and similar to them approximative characteristics of the Nikol'skii-Besov-type classes $B^{Ω}_{p,θ}$ of periodic functions of one and several variables in the space $B_{∞,1}$. We observe, that in the multivariate case $(d≥2)$ the orders of orthowidths of the considered functional classes are realized by their approximations by step hyperbolic Fourier sums that contain the necessary number of harmonics. In the univariate case, an optimal in the sense of order estimates for orthowidths of the corresponding functional classes there are the ordinary partial sums of their Fourier series. Besides, we note that in the univariate case the estimates of the considered approximative characteristics do not depend on the parameter $θ$. In addition, it is established that the norms of linear operators that realize the order of the best approximation of the classes $B^{Ω}_{p,θ}$ in the space $B_{∞,1}$ in the multivariate case are unbounded.